Hanefilere göre (İllet'te) te'sir teorisi. - (:unkn) unknown (My University, 2014)
Bu makalenin amacı, Hanefilerin illet konusundaki görüşlerini tümevarım metodu ile inceleyip onların te'sir teorisini ortaya çıkarmaktır. Bu çalışmada sadece Hanefilerin usûl eserleri dikkate alınmıştır. Makelemiz iki bölümden oluşmaktadır. Birinci bölümde bir sonraki bölümde ele alınacak teısir konusuna zemen teşkil eden illet tanımları kısaca tahlil edilmiştir. Mekalenin esasını teşkil eden ikinci bölümde ise teısir toerisinin Iraklı Hanefilerin ellinde ortaya çıkışına daha sonra Buharaıdaki Hanefilerin buna katkılarına ve son olarak teısir toersinin müteahhirîn dönemi Hanefileri tarafından geliştirilmesine temas edilmiştir.

This research aims to elaborate the theory of effectiveness (ta'thir) of causality (illa) in the Hanafi school. This is carried out through the induction of different opinions from Hanafi scholars in the subject of effectiveness (ta'thir) of causality (illa). The study confines to Usûl al-fiqh literature of Hanafi school. The research consists of two sections. The first section deals with the views of Hanafi scholars regarding causality (illa) as well as their definitions in a summarized form. The importance of this section is reflected through the role it plays, of forming the ground basis for the theory of effectiveness (ta'thir) in the second section. The second section forms the core of research. It focuses on the phases of evolution of effectiveness (ta'thir) theory in Hanafi school. It discusses genesis, development, and culmination of the concept of effectiveness (ta'thir) theory through out Hanafi legal theory.
Theory of effectiveness (ta'thir) of causality (illa) in the legal theory of Hanafi school.
Keywords: Din Bilimi